Regional differences and distributional dynamic evolution of science and technology innovation driven green development efficiency in Chinese agriculture - Lingling Wang; Min Li; Panpan Zhang (Frontiers in Sustainable Food Systems)
IntroductionAgricultural production in China faces mounting environmental pressures, including resource depletion, chemical pollution, and carbon-intensive practices, which threaten ecological sustainability. Agricultural science, technology and innovation (ASTI) is a key lever for harmonizing agricultural growth and green transformation, but its efficiency remains unevenly distributed across regions. This study assesses the spatiotemporal efficiency of ASTI in promoting green agricultural development across 30 Chinese provinces, aiming to uncover persistent regional disparities and dynamic evolution patterns.MethodsConstructing an evaluation model and indicator system for science, technology and innovation driven green development in agriculture, applying the network Slack-Based Measure (SBM) model to measure the level of efficiency, and analyzing regional differences and dynamic features through the Theil index, kernel density estimation and spatial Markov methods.Results and discussionThis study explores the regional differences and distributional dynamic evolution of the efficiency of Agricultural science and technology innovation (ASTI) driven green development in China. The regional efficiency level of each province from 2013 to 2022 was measured by constructing a network SBM model. The results show a clear regional imbalance, with the eastern region showing higher efficiency due to strong investment in innovation and policy coordination effects, while the central and western regions are lagging behind due to fragmented resource allocation and weak institutional support. There is a clear trend of multi-polarization in the kernel density curve, influenced by spatial agglomeration effects and green infrastructure investments; the spatial Markov transformation highlights path dependence and neighborhood effects, emphasizing the role of cross-regional technology diffusion. The integrated approach validates consistency with empirical realities and provides targeted insights for optimizing synergies between ASTI and agriculture, bridging regional gaps, and promoting a spatially coordinated green transition.